1995
DOI: 10.1177/00220345950740080501
|View full text |Cite
|
Sign up to set email alerts
|

Full- vs. Partial-mouth Disinfection in the Treatment of Periodontal Infections: Short-term Clinical and Microbiological Observations

Abstract: In a standard periodontal treatment strategy with consecutive root planings (per quadrant at a one- to two-week interval), re-infection of a disinfected area might occur before completion of the treatment. This study examines, both clinically and microbiologically, whether a full-mouth disinfection within 24 hours significantly improves the outcome of periodontal treatment. Ten patients with advanced chronic periodontitis were randomly allocated to a test and a control group. The patients from the control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
400
5
21

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 342 publications
(443 citation statements)
references
References 36 publications
17
400
5
21
Order By: Relevance
“…Vandekerckhove et al 31 reported eight months' follow up of the Quirynen et al 17 study. Higher reduction in probing depth was reported for the FMD group in initially moderate and deep pockets but this was statistically signifi cant only for the deep (≥7 mm) category (p = 0.01).…”
Section: Comparisons Of Full-mouth Disinfection (Fmd) V Quadrant Scalmentioning
confidence: 99%
See 4 more Smart Citations
“…Vandekerckhove et al 31 reported eight months' follow up of the Quirynen et al 17 study. Higher reduction in probing depth was reported for the FMD group in initially moderate and deep pockets but this was statistically signifi cant only for the deep (≥7 mm) category (p = 0.01).…”
Section: Comparisons Of Full-mouth Disinfection (Fmd) V Quadrant Scalmentioning
confidence: 99%
“…Mongardini et al 1999 36 The clinical data were reported in another study that is included (Quirynen et al 2000) 30 Quirynen et al 1995 17 The duration of the study less than six months. However, the long-term follow-up of the patients was reported in another study that is included 31 Quirynen et al 1998 37 Only microbiological data were reported …”
Section: Reason(s) For Exclusionmentioning
confidence: 99%
See 3 more Smart Citations